2007
DOI: 10.1093/jac/dkm412
|View full text |Cite
|
Sign up to set email alerts
|

Highly active antiretroviral therapy and incidence of cervical squamous intraepithelial lesions among HIV-infected women with normal cytology and CD4 counts above 350 cells/mm3

Abstract: Objectives: To provide evidence for the long-term effect of highly active antiretroviral therapy (HAART) on the incidence of cervical squamous intraepithelial lesions (SILs) among HIV-positive women with normal cytology test and CD4 count above 350 cells/mm 3 .Patients and methods: A retrospective cohort study was carried out in HIV-positive women with two consecutive normal cervical cytological tests (Papanicolaou test) and at least one subsequent test, without previous cervical history of SIL or cancer diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 9 publications
2
32
1
Order By: Relevance
“…Within study comparisons, however, show that in 6 studies, lower CD4 count was associated with an increased incidence of abnormal cervical cytology 7,10,19,21,26,27 , although most estimates were not statistically significant. Two studies assessed nadir CD4 counts and reported no statistically significant relationship with incidence 29,31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within study comparisons, however, show that in 6 studies, lower CD4 count was associated with an increased incidence of abnormal cervical cytology 7,10,19,21,26,27 , although most estimates were not statistically significant. Two studies assessed nadir CD4 counts and reported no statistically significant relationship with incidence 29,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Though one study showed a reduction in incidence with HAART use versus non-HAART use 22 , most studies found no significant difference between HAART/ART use and non-use 19,26,31,32 . Associations may be confounded by the practice of initiating ART use only in patients with low CD4 counts or lack comparability due to differences in CD4 count recovery, HIV viremia, and follow-up time after ART initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also differed in their treatment of atypical squamous cells of undetermined significance (ASCUS). Some considered a change of cytology result from low grade SIL (LSIL) to ASCUS as regression, [13] others resolved diagnoses of ASCUS with colposcopy and histology,[27] and still others left ASCUS diagnoses out of analysis[28]. …”
Section: Resultsmentioning
confidence: 99%
“…In a well-characterized French cohort with a median follow-up period of 28 months, there was no independent effect of receiving antiretroviral therapy or restored immune status (evidenced by higher CD4+ T-cell counts) on incident SIL, which were significantly associated only with being in the 30-39 years age group[22]. In a retrospective analysis of a cohort from Spain of HIV-infected women with CD4+ cell counts >350 cells/mm 3 and with no previous SIL, there was no significant difference in SIL incidence between groups receiving versus not receiving HAART[28]. …”
Section: Resultsmentioning
confidence: 99%
“…Compared to those who are not on HAART, HIV-infected women on antiretroviral therapy tend to have a lower incidence rate of SILs [2] and higher probability of remaining free of SILs [21]. However, the effect of HAART on changes of SILs remains unclear and controversial.…”
Section: Discussionmentioning
confidence: 99%